Polycomb repressive complex 1 modifies transcription of active genes - Pherson, Michelle (Sci Adv, 2017)
This study examines the role of Polycomb repressive complex 1 (PRC1) at active genes. The PRC1 and PRC2 complexes are crucial for epigenetic silencing during development of an organism. They are recruited to Polycomb response elements (PREs) and establish silenced domains over several kilobases. Recent studies show that PRC1 is also directly recruited to active genes by the cohesin complex. Cohesin participates broadly in control of gene transcription, but it is unknown whether cohesin-recruited PRC1 also plays a role in transcriptional control of active genes. We address this question using genome-wide RNA sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq). The results show that PRC1 influences transcription of active genes, and a significant fraction of its effects are likely direct. The roles of different PRC1 subunits can also vary depending on the gene. Depletion of PRC1 subunits by RNA interference alters phosphorylation of RNA polymerase II (Pol II) and occupancy by the Spt5 pausing-elongation factor at most active genes. These effects on Pol II phosphorylation and Spt5 are likely linked to changes in elongation and RNA processing detected by nascent RNA-seq, although the mechanisms remain unresolved. The experiments also reveal that PRC1 facilitates association of Spt5 with enhancers and PREs. Reduced Spt5 levels at these regulatory sequences upon PRC1 depletion coincide with changes in Pol II occupancy and phosphorylation. Our findings indicate that, in addition to its repressive roles in epigenetic gene silencing, PRC1 broadly influences transcription of active genes and may suppress transcription of nonpromoter regulatory sequences.